The effect of omega-3 fatty acid supplementation on Nitric oxide (NO) serum levels and anthropometric indices in men with cardiovascular disease referred to Tehran Heart Center: A randomized, double-blind, placebo-controlled trial - Zarei, Mahnaz; Ansari, Samaneh; Baghdadi, Ghazal (Researcher Bulletin of Medical Sciences, 2025)
Objective: Cardiovascular diseases (CVDs) are among the most common non-communicable diseases. They are the leading cause of death worldwide. Omega-3 unsaturated fatty acids are not produced in the human body, so they are essential for humans and are vital for the regulation of human performance. The aim of this study was to evaluate the effect of omega-3 fatty acid supplementation on Nitric oxide (NO) serum levels and anthropometric indices in men with cardiovascular disease. Materials and Methods: In this double-blind study, 40 male Wistar rats were divided into 4 groups (N: 10). The groups were: Control group, supplement group, exercise group, and exercise + supplement group. At the end, blood was drawn from all the animals, then the serum lipid profile, were measured by ELISA method. They were analyzed with SPSS and a significance level of <0.05. Results: No statistically significant difference was observed in any of the anthropometric indicators and blood pressure levels (systolic and diastolic) before and after the intervention, as well as within the groups. Also, no significant difference was observed in the serum level of NO before and after the start of the study in both groups, and within each group before and after the intervention, there was no statistically significant difference (P>0.05). Conclusion: The findings of the present study showed that 10 weeks of supplementing with omega-3 supplementation at a dose of 4 grams per day, didn’t cause any significant changes in serum levels of NO